Inhibition of synaptosome membrane-bound integral enzymes by organic solvents. - Korpela, Marja (Scandinavian Journal of Work, Environment & Health, 1989)
The possible mechanism of the depressive effect of organic solvents on the central nervous system (CNS) was studied with synaptosome membranes as a model. The changes in the activities of the membrane-bound integral enzymes acetylcholinesterase, total adenosinetriphosphatase, and magnesium-activated adenosinetriphosphatase were determined after treatment with different concentrations of organic solvents in vitro. Aromatic hydrocarbons and chlorinated aliphatic hydrocarbons inhibited all the enzyme activities concentration dependently. Alcohols had no significant effect at the same dose levels. The results of the present study suggest that the CNS depressive effect of organic solvents may be based on their interaction with membrane integral proteins.